Channel Estimation for SM Systems over Time-Varying Rayleigh Fading Channels - Doğan, Hakan; Panayırcı, Erdal; ACAR, YUSUF (IEEE, 345 E 47Th St, New York, Ny 10017 Usa, 2014)
This paper is concerned with the challenging and timely problem of channel estimation for spatial modulated systems in the presence of time varying channels. Recently, estimation of channel state information for SM systems is investigated by the recursive least square (RLS) algorithm for slow fading channels. However, it is clear that the RLS based receiver will have a performance degradation for fast fading channels. Therefore, we developed iterative channel estimation based on detected symbols and curve fitting to track the channel variations for SM systems. Simulation results have demonstrated that the proposed iterative channel estimation offer substantial performance gains over the RLS channel estimation. In particular, a savings of about 4dB is obtained at BER = 10(-7), as compared with RLS based receiver at 150km/h for 2 x 4 single carrier SM systems.
Keywords: Spatial Modulation; Channel Estimation; MIMO; Iterative Receiver